Workplace Anxiety as a Bridge Between Job Insecurity and Work-Life Conflict: Insights from Healthcare Employees - Pratama, Rohmawan Adi; Purwati, Purwati; Novita Sari, Indah; Puspita Rachma, Ulfa; Khoirun Nikmah, Filda (Bulletin of Counseling and Psychotherapy, 2025)
This research intends to examine the effect of role stress and job insecurity on job burnout and nurses' performance in hospitals. Apart from this, this research also explores the mediating role of workplace anxiety in the context of the bond between job insecurity and work-life conflict. Using a quantitative approach with a cross-sectional design, information was gathered by means of a survey of 160 nurses at One of the private hospitals in Surakarta. The analysis was conducted using the SEM-PLS method. The results showed that role stress had a positive effect on job burnout, while job burnout had a negative impact on nurses' performance. In addition, role stress also had a significant direct negative effect on nurses' performance. Job insecurity was found to have a positive contribution to job burnout and a negative effect on nurses' performance. Workplace anxiety was shown to be a significant mediator in the the correlation between employment insecurity and work-life conflict. These findings confirm that job stress and job uncertainty are the main factors that negatively impact nurses' well-being and performance. Therefore, an effective managerial strategy is needed to reduce work pressure, increase job security, and provide psychological support for health workers in order to improve the quality of health services.